THE ANALYSIS OF RELIGIOSITY AND COUNTRY OF ORIGIN INFLUENCE TOWARDS PURCHASE INTENTION WITH CONSUMER ATTITUDES AS THE INTERVENING VARIABLE IN KFC PANDANARAN SEMARANG (CASE STUDY IN FE UNISSULA’S STUDENTS) - Edwin Hermanto (UNISSULA, 2018)
This research aims to analyze the influence of religiosity and the county of origin against the purchase intention in KFC Pandanaran Semarang with consumer attitudes as intervening variable. The population in this research is a college student of economic faculty of Islamic University of Sultan Agung. The technique of the sample with a purposive sampling method and incidental sampling.Samples taken as many as 100 collage students, with a research instrument in the form of a questionnaire.Data analysis using SPSS 23.0. The results showed that religiosity and country of origin has a positive and significant effect on consumer attitudes. Country of origin and consumer attitudes has a positive and significant effect on the purchase intention. Religiosity has a negative and significant effect on purchase intention. Consumer attitudes not as intervening variables between religiosity towards purchase intention and between the country of origin towards purchase intention.Keywords: Religiosity, Country of origin, Consumer attitudes, and Purchase intention.